The Scope of Sectarian Tolerance in Islam - Bishi, Mohammad (Jordan Journal of Islamic Studies, 2023)
The research aims to reveal the limits of the ordinary and the exceptional in the Islamic sectarian relations that have changed in quantity and quality and the process of the conflicting doctrinal history of the Christian religion. The research raises a basic hypothesis, which is the broad limits of authenticity in tolerance and coexistence among Muslims, and the diminution of the contrast in the exceptional and non-coexistent history. In it, we used the inductive analytical and descriptive approaches, and concluded by proposing ways to overcome the dilemmas of exceptional history in the scientific, doctrinal and media reality in order to invest tolerance and coexistence, and to study the exceptional sermon and consideration for the survival and arrangement of the social structure of the vast Islamic lands.